Optimal timing of tau pathology imaging and automatic extraction of a reference region using dynamic [(18)F]THK5317 PET - Jonasson, My (Neuroimage Clin, 2019)
[(18)F]THK5317 is a PET tracer for in-vivo imaging of tau associated with Alzheimer's disease (AD). This work aimed to evaluate optimal timing for standardized uptake value ratio (SUVR) measures with [(18)F]THK5317 and automated generation of SUVR-1 and relative cerebral blood flow (R(1)) parametric images. Nine AD patients and nine controls underwent 90 min [(18)F]THK5317 scans. SUVR-1 was calculated at transient equilibrium (TE) and for seven different 20 min intervals and compared with distribution volume ratio (DVR; reference Logan). Cerebellar grey matter (MRI) was used as reference region. A supervised cluster analysis (SVCA) method was implemented to automatically generate a reference region, directly from the dynamic PET volume without the need of a structural MRI scan, for computation of SUVR-1 and R(1) images for a scan duration matching the optimal timing. TE was reached first in putamen, frontal- and parietal cortex at 22 ± 4 min for AD patients and in putamen at 20 ± 0 min in controls. Over all regions and subjects, SUVR(20–40)-1 correlated best with DVR-1, R(2) = 0.97. High correlation was found between values generated using MRI- and SVCA-based reference (R(2) = 0.93 for SUVR(20–40)-1; R(2) = 0.94 for R(1)). SUVR(20–40) allows for accurate semi-quantitative assessment of tau pathology and SVCA may be used to obtain a reference region for calculation of both SUVR-1 and R(1) with 40 min scan duration.